HUBUNGAN ANTARA EMPATI DENGAN KEENDERUNGAN PERILAKU PROSOSIAL PERAWAT DI RUMAH SAKIT Tk III 04.06.03 Dr.SOETARTO YOGYAKARTA - Noor Ika Widaningsih; Indriyati Eko Purwaningsih (JURNAL SPIRITS, 2015)
ABSTRACT One of task from a nurse at the hospital is doing observation in every patient, if nusre do not have asanse of sincare to help, so patient’s recovery will not be achieved optimally. This study aims to determine the relationship between empathy and prosocial behavior tendences in nurse at Tk. III 04.06.03 Dr.SOETARTO hospital Yogyakarta.Research subject 90 is a male and female nurse at the patient unit. The method used in this study is testing methode, this method being use with make a number of statement that need to be answered by the subject. Preparation of scale models used in this research is use a sumatied rating.The result in this research with  correlation analysis of moment product rom pearson, correlation was obtained between the two variabel (rxy) = 0,439 and p 0,000 (p<0,001) with contribution from independen and dependen variabel 19,2% and 80,8% other variabel that there are other variabel that can affect social behavior tendencies. Keywords: empathy, prosocial behavior tendencies nurse